2007
DOI: 10.1016/j.rmed.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality after an asthma admission: A national United Kingdom database analysis

Abstract: Co-morbid conditions experienced by older asthma patients may contribute to mortality post an asthma admission and greater understanding of risk factors contributing to fatality are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
4
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 27 publications
8
65
4
2
Order By: Relevance
“…The mortality rate among patients hospitalized in Spain and Latin America was similar to that found in previous studies conducted in the United States and the United Kingdom (less than 1% of all admissions). (12)(13) Most of the patients who died were over 34 years of age. In addition, recent studies have reported that the incidence of asthma-related in-hospital mortality is higher among women than among men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mortality rate among patients hospitalized in Spain and Latin America was similar to that found in previous studies conducted in the United States and the United Kingdom (less than 1% of all admissions). (12)(13) Most of the patients who died were over 34 years of age. In addition, recent studies have reported that the incidence of asthma-related in-hospital mortality is higher among women than among men.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have reported that the incidence of asthma-related in-hospital mortality is higher among women than among men. (13)(14)18) Although it is difficult to understand why the mortality risk is greater for female patients hospitalized for asthma, it might be due to the gender bias (predominance of females) among adults with asthma. Among patients with severe asthma, the female/male ratio can be as high as 4:1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Статистика смертности больных БА в РФ неизвестна, поэтому при моделировании была использована экстра-поляция риска смерти по сравнению с обычной популя-цией у больных БА в Великобритании на основе открытых данных [26]. Средневзвешенный по возрастным группам риск смерти для больных БА вне обострения по отноше-нию к обычной популяции в Великобритании составил 0,8 (что интерпретировалось нами как отсутствие разли-чий), а во время астматического статуса риск смерти был повышен в 5,7 раз.…”
Section: смертностьunclassified